2015
DOI: 10.1074/jbc.m114.612622
|View full text |Cite
|
Sign up to set email alerts
|

Complement 5a Enhances Hepatic Metastases of Colon Cancer via Monocyte Chemoattractant Protein-1-mediated Inflammatory Cell Infiltration

Abstract: Background: It is known that the complement system contributes to tumor progression, but the exact mechanism is still unclear. Results: Complement 5a enhances tumor metastasis via monocyte chemoattractant protein-1-mediated inflammatory cell infiltration. Conclusion: Complement 5a plays a pro-metastasis role by establishing an inflammatory microenvironment required for tumor metastasis. Significance: Our results provide a therapeutic insight for complement in treatment of malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 47 publications
1
66
1
1
Order By: Relevance
“…45,46 Moreover, C5a produced from cancer cells tends to generate an immunosuppressive tumor microenvironment and is related to tumor angiogenesis. 47 It is reported that cancers with overexpression of C5aR are considered aggressive and have poor prognosis.…”
Section: Combination Strategiesmentioning
confidence: 99%
“…45,46 Moreover, C5a produced from cancer cells tends to generate an immunosuppressive tumor microenvironment and is related to tumor angiogenesis. 47 It is reported that cancers with overexpression of C5aR are considered aggressive and have poor prognosis.…”
Section: Combination Strategiesmentioning
confidence: 99%
“…In addition, C5a favored liver metastasis by promoting tumor inflammation. Indeed, genetic deficiency of C5aR leads to impaired production of CCL2 (Piao et al, 2015). Finally, data obtained studying pathologies not related to cancer raise the possibility that Complement proteins may enhance Epithelialmesenchymal transition (EMT), provide chemotactic stimuli (i.e., C5a and C3a; Pasinetti et al, 1996), and induce production of growth factors (i.e., VEGF and TGF-β; Nozaki et al, 2006), which prime and encourage tumor invasion and migration (Christofori, 2006).…”
Section: Macrophages In Complement-mediated Ptx3-regulated Tumor Promentioning
confidence: 96%
“…Le C5a est également associé à la formation de métas-tases. Dans un modèle murin de cancer colorectal, une diminution du nombre de métastases hépatiques est observée chez des souris déficientes pour le gène codant le récepteur C5aR, par rapport aux souris sauvages [23]. Ce potentiel métastatique aurait pour origine une modulation par le C5a de la capacité invasive des cellules.…”
Section: Synthèse Revuesunclassified